Tumor necrosis factor receptor 1 gain‐of‐function mutation aggravates nonalcoholic fatty liver disease but does not cause insulin resistance in a murine model12*. Issue 2 (10th January 2013) - Aparicio‐Vergara, Marcela; Hommelberg, Pascal P.H.; Schreurs, Marijke; Gruben, Nanda; Stienstra, Rinke; Shiri‐Sverdlov, Ronit; Kloosterhuis, Niels J.; de Bruin, Alain; van de Sluis, Bart; Koonen, Debby P.Y.; Hofker, Marten H.
Abstract Ectodomain shedding of tumor necrosis factor receptor 1 (TNFR1) provides negative feedback to the inflammatory loop induced by TNFα. As the significance of this mechanism in obesity‐associated pathologies is unclear, we aimed to unravel how much TNFR1 ectodomain shedding controls the development of nonalcoholic fatty liver disease (NAFLD), as well as its role in the development of insulin resistance. We used knockin mice expressing a mutated TNFR1 ectodomain (p55Δns), incapable of shedding and dampen the inflammatory response. Our data show that persistent TNFα signaling through this inability of TNFR1 ectodomain shedding contributes to chronic low‐grade inflammation, which is confined to the liver. In spite of this, hepatic lipid levels were not affected by the nonshedding mutation in mice fed a chow diet, nor were they worse off following 12 weeks of high‐fat diet (HFD) than controls (p55+/+) fed an HFD. We detected inflammatory infiltrates, hepatocellular necrosis, and apoptosis in livers of p55Δns/Δns mice fed an HFD, suggesting advanced progression of NAFLD toward nonalcoholic steatohepatitis (NASH). Indeed, fibrosis was present in p55Δns/Δns mice, but absent in wildtype mice, confirming that the p55Δns/Δns mice had a more severe NASH phenotype. Despite low‐grade hepatic inflammation, insulin resistance was not observed in p55Δns/Δns mice fed a chow diet, and HFD‐induced insulin resistance was no worse in p55Δns/Δns mice than p55+/+ mice. Conclusion: TNFR1 ectodomain shedding is not an essential feedback mechanism in preventing the development of hepatic steatosis or insulin resistance. It is, however, pivotal in attenuating the progression from "simple steatosis" towards a more serious phenotype with many NASH features. Targeting TNFR1 could therefore be beneficial in attenuating NASH. (HEPATOLOGY 2013)